(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article deals with the features of word formation structure and semantics of nominal confixal derivatives with -ок - names of subjects in diachronical aspect, which are fixed in middle and new Ukrainian language. Seventeen confixal morphemes with postposition part -ок takes part in formation of such derivative words. In view of it the statement of a material is carried out in a direction to reduction of efficiency word formation types.